Do Differences in Latitudinal Distributions of Species and Organelle Haplotypes Reflect Thermal Reaction Norms Within the Emiliania/Gephyrocapsa Complex? - von Dassow, Peter; Muñoz Farías, Paula Valentina; Pinon, Sarah; Velasco-Senovilla, Esther; Anguita-Salinas, Simon (Frontiers in Marine Science, 2021)
The cosmopolitan phytoplankter Emiliania huxleyi contrasts with its closest relatives that are restricted to narrower latitudinal bands, making it interesting for exploring how alternative outcomes in phytoplankton range distributions arise. Mitochondrial and chloroplast haplogroups within E. huxleyi are shared with their closest relatives: Some E. huxleyi share organelle haplogroups with Gephyrocapsa parvula and G. ericsonii which inhabit lower latitudes, while other E. huxleyi share organelle haplogroups with G. muellerae, which inhabit high latitudes. We investigated whether the phylogeny of E. huxleyi organelles reflects environmental gradients, focusing on the Southeast Pacific where the different haplogroups and species co-occur. There was a high congruence between mitochondrial and chloroplast haplogroups within E. huxleyi. Haplogroup II of E. huxleyi is negatively associated with cooler less saline waters, compared to haplogroup I, both when analyzed globally and across temporal variability at the small special scale of a center of coastal upwelling at 30° S. A new mitochondrial haplogroup Ib detected in coastal Chile was associated with warmer waters. In an experiment focused on inter-species comparisons, laboratory-determined thermal reaction norms were consistent with latitudinal/thermal distributions of species, with G. oceanica exhibiting warm thermal optima and tolerance and G. muellerae exhibiting cooler thermal optima and tolerances. Emiliania huxleyi haplogroups I and II tended to exhibit a wider thermal niche compared to the other Gephyrocapsa, but no differences among haplogroups within E. huxleyi were found. A second experiment, controlling for local adaptation and time in culture, found a significant difference between E. huxleyi haplogroups. The difference between I and II was of the expected sign, but not the difference between I and Ib. The differences were small (≤1°C) compared to differences reported previously within E. huxleyi by local adaptation and even in-culture evolution. Haplogroup Ib showed a narrower thermal niche. The cosmopolitanism of E. huxleyi might result from both wide-spread generalist phenotypes and specialist phenotypes, as well as a capacity for local adaptation. Thermal reaction norm differences can well explain the species distributions but poorly explain distributions among mitochondrial haplogroups within E. huxleyi. Perhaps organelle haplogroup distributions reflect historical rather than selective processes.